Correlation Of Chronic Low Back Pain and Core Muscle Weakness Among Taxi Car Drivers - Zacharia, Amal.P.; Varadharajulu, G. (Journal of Neonatal Surgery, 2025)
Background: : Chronic low back pain (CLBP) is a widespread, debilitating condition affecting millions globally, particularly in high-risk occupations like taxi driving. Taxi drivers are prone to CLBP due to prolonged sitting, poor posture, repetitive motions, and exposure to whole-body vibrations, leading to core muscle weakness. Weak core muscles destabilize the spine, increasing strain on the lower back and exacerbating pain. The sedentary nature of driving, coupled with job-related stress, worsens muscle deconditioning, creating a cycle of pain and inactivity. Addressing core muscle weakness through targeted interventions can alleviate CLBP and improve taxi drivers' overall health. AIM :To study about the correlation of chronic low back pain and core muscle weakness among taxi car drivers METHODOLOGY: the study focused on individuals driving for two years, Age criteria was between 30- 60 years , and Individuals who work as taxi car drivers. The study was a survey method. A total of 81 participants were selected using a simple random sampling technique. The study was conducted in karad. The duration of the study was 6 months. RESULT: The data shows that prolonged driving increases pain at rest and during activity, while decreasing muscle strength and core endurance. Drivers with longer hours (16-20) experience more pain, lower muscle strength, and reduced endurance, highlighting the need for targeted core training to prevent muscle deconditioning and injury. CONCLUSION: The correlation between CLBP and core muscle weakness in taxi drivers is evident through various contributing factors such as prolonged sitting, poor posture, repetitive driving motions, and exposure to whole-body vibrations. These occupational demands lead to core muscle deconditioning, particularly in the deep stabilizing muscles that support the lumbar spine. As core muscles weaken, the spine becomes less stable, increasing mechanical stress on the lower back, which exacerbates CLBP..